A screening of lipophilic antioxidants in muscle tissue of cage reared bluefin tuna (Thunnus thynnus thynnus L.): A potential tool to assess oxidative stress - Ferrante I.; Cataudella S.; Di Marco P.; Passi S.; Ricci R.; Bertolino F. (Domestication of the bluefin tuna Thunnus thynnus thynnus, 2003)
Oxidative stress research in aquaculture is particularly important in the assessment of both the health of farmed fish and the quality of sea food. Lipophilic antioxidant levels in relation to fatty acid patterns of total lipids in muscle tissue of Thunnus thynnus were investigated. Significant differences in ubiquinol-ubiquinone and alpha-tocopherol content are well characterising white and red muscle, in relation to their different energetic metabolism. Variations in lipophilic antioxidant levels may represent a specific oxidative stress marker in relation to alteration in swimming behaviour.
1. International Symposium on Domestication of the Bluefin Tuna Thunnus Thynnus Thynnus, 2002/02/03-08, Cartagena (Spain)